2018
DOI: 10.1097/igc.0000000000001222
|View full text |Cite
|
Sign up to set email alerts
|

Treatment Patterns and Health Outcomes in Platinum-Refractory or Platinum-Resistant Ovarian Cancer: A Retrospective Medical Record Review

Abstract: Current treatments for PRROC yield limited PFS and frequent hospitalizations reported to be related to toxicities or procedural complications, suggesting a continued unmet need for more effective and tolerable therapeutic strategies for PRROC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 14 publications
4
11
0
Order By: Relevance
“…For platinum-resistant/platinumrefractory relapse, sequential single-agent salvage chemotherapy is superior to multiagent chemotherapy which increases toxicity without clear bene ts; however, no priority sequence of these single agents is recommended [5]. As previously mentioned, PLD is the most common initial therapy in the real world [6]. In this preliminary analysis, though the total sample size was 67 (less than 78), 20 patients had achieved an objective response.…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…For platinum-resistant/platinumrefractory relapse, sequential single-agent salvage chemotherapy is superior to multiagent chemotherapy which increases toxicity without clear bene ts; however, no priority sequence of these single agents is recommended [5]. As previously mentioned, PLD is the most common initial therapy in the real world [6]. In this preliminary analysis, though the total sample size was 67 (less than 78), 20 patients had achieved an objective response.…”
Section: Discussionmentioning
confidence: 78%
“…Patients with platinum-refractory or resistant relapse were assessed with a Simon's two-stage design with a two-sided an error of 5% and a power of 80% [15]. Previous studies indicated that objective response rate of PLD monotherapy in patients with platinum-refractory or resistant relapse was 15% − 40.4% [6,16], and we initially expected that the objective response rate of PLD in these patients would be 30%. Therefore, we set P0 to 15%, and P1 to 30% in this study.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A larger dose expansion cohort would have more clearly characterized disease response. PPROC comprises a small subset ($10%) of patients with EOC with a dismal survival outcome (14). The scarcity of these patients meant that the PPROC-only cohort failed to recruit and was eventually closed.…”
Section: Discussionmentioning
confidence: 99%
“…13 Novartis Pharma AG, Basel, Switzerland. 14 Sir Charles Gairdner Hospital, Nedlands, Western Australia, Australia.…”
Section: ) Inhibitors Of the Upstream Kinase Mtorc1 Have Been Shown mentioning
confidence: 99%